2014
DOI: 10.1177/1533317514523487
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Entorhinal Cortex in Alzheimer’s Disease

Abstract: The incidence of Alzheimer's disease (AD) has been increasing in the recent years but the underlying mechanisms remain uncertain. This study aimed to analyze the differentially expressed genes (DEGs) in entorhinal cortex with AD and identify featured genes related to AD. Gene expression profile GSE5281 was downloaded from Gene Expression Omnibus, including 10 AD and 13 control samples. Differentially expressed genes were identified by Student t test including 119 upregulated and 591 downregulated DEGs. Then, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
0
22
1
Order By: Relevance
“…The glycolysis pathway is related to VaD, and genes involved in this pathway, such as GPI and GAPD, are significantly downregulated in the AD hippocampus [31,35]. In addition, PFKM, PGM1, ALDOA, and ALDOC are also downregulated in the entorhinal cortex of AD patients [32,36,37]. Our study showed that downregulated proteins were significantly enriched in the subpathways of the ‘glycolysis/gluconeogenesis' pathway.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The glycolysis pathway is related to VaD, and genes involved in this pathway, such as GPI and GAPD, are significantly downregulated in the AD hippocampus [31,35]. In addition, PFKM, PGM1, ALDOA, and ALDOC are also downregulated in the entorhinal cortex of AD patients [32,36,37]. Our study showed that downregulated proteins were significantly enriched in the subpathways of the ‘glycolysis/gluconeogenesis' pathway.…”
Section: Discussionmentioning
confidence: 89%
“…The downregulated ATP5B in the AD hippocampus leads to a reduction in the levels of energy metabolism [31]. In addition, Ding et al [32] proved that the ATP metabolism network comprises many downregulated genes such as ATP5B, ATP5C1, and ATP5G1 in the entorhinal cortex of AD. In this study, ‘metabolic pathways' and the ‘Alzheimer's disease' pathway were the significant pathways identified in the pathway crosstalk network.…”
Section: Discussionmentioning
confidence: 99%
“…the transcriptional response associated with its onset and progression (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). These studies have revealed that this transcriptional response involves genes corresponding to proteins that can cause the disease and those associated with the cellular processes engaged in combating it (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that this transcriptional response involves genes corresponding to proteins that can cause the disease and those associated with the cellular processes engaged in combating it (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…However, this concept has been recently challenged111213. In fact, in addition to mitochondrial respiratory enzyme defects, increasing evidence implicates the dysfunction of mitochondrial F1FO-ATP synthase in AD14151617.…”
mentioning
confidence: 99%